A method for preparing agglomerated diamond
The diamond powder is treated by nickel powder etching, silanization and zinc oxide coating, and agglomerated diamond is prepared in combination with ceramic bonding agent, which solves the problems of poor self-sharpness and difficult to control the cutting depth in precision processing, and achieves higher mechanical strength and wear resistance.
Patent Information
- Application Number
- CN202411390551.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-10-08
AI Technical Summary
Traditional diamond abrasives have problems in the field of precision processing, such as poor self-sharpness and difficult to control the cutting depth, which is difficult to meet the needs of high-precision processing.
The diamond powder was etched by nickel powder, and silanization and zinc oxide coating were carried out to prepare agglomerated diamonds in combination with ceramic bonding agent.
The mechanical strength, wear resistance, bond strength and oxidation resistance of agglomerated diamonds are improved, making them perform better in high-precision processing.
Smart Images

Figure CN119220222B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic polishing materials, and in particular to a method for preparing agglomerated diamonds. Background Art
[0002] With the rapid development of modern industrial technology, especially in the fields of rail transportation, 5G communication technology, and new material processing, the requirements for workpiece processing accuracy are increasing. Ultra-precision grinding and polishing technology has become a hot topic in current research, and grinding tools with high grinding efficiency, low environmental pollution and low surface roughness have become a new development trend. Traditional diamond abrasives have disadvantages such as poor self-sharpening and difficult to control cutting depth in the field of precision machining, which makes it difficult to meet the needs of high-precision machining. As a new type of superhard material, agglomerated diamond has gradually attracted attention due to its unique spherical multi-edge angle characteristics, which can maintain high grinding forces without scratching during the grinding and polishing process.
[0003] Agglomerated diamond is a high-performance grinding and polishing material, which is made of agglomerated diamond powder with a special formula. Agglomerated diamond powder is a spherical abrasive made of diamond powder and binder through special processing. Diamond powder can be prepared in various ways, including high temperature and high pressure method, detonation method, crushing method, laser shock method, catalytic reduction method, chemical vapor deposition method, etc. Agglomerated diamond has the characteristics of sustainable grinding, stable grinding and polishing effect, fast cutting rate, good surface consistency and high processing efficiency. It is suitable for grinding and polishing of materials such as computer heads, sapphire, silicon carbide substrates, optical fiber connectors, ceramics, crystals, optical glass, etc. It has broad application prospects in semiconductors, metal processing, ceramics and other fields. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for preparing agglomerated diamond, aiming to prepare agglomerated diamond with better mechanical strength so as to have better application prospects.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] A method for preparing agglomerated diamond, the method comprising the following steps:
[0007] Step 1, etching diamond micropowder with nickel powder to prepare etched diamond micropowder, performing surface silanization treatment on the etched diamond micropowder to prepare silanized diamond micropowder, and then coating the etched diamond micropowder with zinc oxide to prepare coated diamond micropowder;
[0008] Step 2, adding 9-10 parts by weight of silanized diamond powder and 8-12 parts by weight of coated diamond powder to 100 parts by weight of diamond powder, mixing the mixture evenly to obtain a mixed diamond powder component, and preparing a ceramic binder using sodium nitrate, boric acid, aluminum nitrate and tetraethyl orthosilicate as raw materials;
[0009] Step 3, weighing 30-50 parts by weight of a mixed diamond powder component and 20-30 parts by weight of a ceramic binder, pouring them into a ball mill to obtain a ball-milled component, weighing 0.1-0.2 parts by weight of polyvinyl alcohol, pouring them into 20-50 parts by weight of pure water, and stirring at a speed of 500 r / min for 10 minutes to obtain a solution component;
[0010] Step 4: Pour the ball-milled component into the solution component and stir at a speed of 200 r / min for 10 minutes. After spray drying, bake and heat-insulate to agglomerate. The agglomerated diamond obtained after sieving is obtained.
[0011] Furthermore, in step 1, the preparation steps of etched diamond powder are:
[0012] Step 2.1, immerse the diamond powder in a hydrochloric acid solution and boil it for 10 minutes, rinse it with pure water until it is neutral, immerse it in a sodium hydroxide solution and boil it for 10 minutes, rinse it with pure water again until it is neutral, and then dry it. The result is recorded as pre-treated diamond powder;
[0013] Step 2.2, the pretreated diamond powder and nickel powder are mixed in a weight ratio of 1:5 and poured into a quartz boat for compaction, and then the quartz boat is placed in a vacuum tube furnace and heated to 600°C at a heating rate of 10°C / min, and then heated to 900°C at a heating rate of 5°C / min, and then cooled to 300°C at a cooling rate of 10°C / min after keeping the temperature for 1 hour, and then naturally cooled to room temperature, and the obtained result is recorded as a sintered component;
[0014] Step 2.3, immerse the sintered component in aqua regia and stir at a speed of 100 r / min for 30 minutes, then place it in an ultrasonic cleaner for ultrasonic oscillation, filter and remove the filtrate to obtain a precipitated component, rinse the precipitated component with pure water to neutrality and dry it to obtain etched diamond micropowder.
[0015] Furthermore, in step 2.1, the mass fraction of the hydrochloric acid solution is 10%, the mass fraction of the sodium hydroxide solution is 10%, and the specific operation of the drying treatment is to dry it at a temperature of 65°C for 2-3 hours. In step 2.3, the specific operation of the ultrasonic oscillation is to ultrasonically oscillate at a power of 200 W for 10 minutes, and the specific operation of the drying treatment is to dry it in an oven at 68°C for 3-5 hours.
[0016] Furthermore, in step 1, the preparation steps of silanized diamond powder are:
[0017] Step 4.1, 5 mL of ethyl orthosilicate and 195 mL of 80% ethanol aqueous solution were stirred at 400 r / min in a water bath at 50°C for 2-3 h, and the resultant was recorded as the hydrolyzate component;
[0018] Step 4.2, weigh 2-3g of etched diamond powder and pour it into the hydrolyzate component, stir and react at a speed of 300r / min in a water bath at 50-80℃ for 2-4h to obtain a suspension, and place the suspension at a temperature of 58℃ to evaporate for 24-48h. The obtained powder is silanized diamond powder.
[0019] Furthermore, in step 1, the preparation steps of coated diamond powder are:
[0020] Step 5.1, weigh 9 g of zinc nitrate and dissolve it in 300 mL of pure water and stir until dissolved, then add 55 g of urea and stir until dissolved, and finally add 45 mg of sodium dodecyl sulfate and stir until dissolved, the result is recorded as zinc nitrate solution;
[0021] Step 5.2, weigh 4-5g of etched diamond powder and add it to zinc nitrate solution, stir magnetically for 30 minutes, heat to 80°C, and stir at a constant temperature for 2 hours to react. After the reaction is completed, filter to obtain the precipitate, rinse with pure water until neutral, and finally place it in a muffle furnace at 300°C for 2 hours. After naturally cooling to room temperature, the obtained is coated diamond powder.
[0022] Furthermore, in step 5.1, the specific operation of stirring until dissolved is stirring at a speed of 400 r / min for 10 min, and in step 5.2, the speed of magnetic stirring is 500 r / min, and the speed of constant temperature stirring is 300 r / min.
[0023] Furthermore, in step 2, the specific operation of mixing uniformly is pouring into a ball mill and ball milling at a speed of 600 r / min for 10 minutes.
[0024] Furthermore, in step 2, the preparation steps of the ceramic binder are:
[0025] Step 8.1, weigh 2-3g sodium nitrate, 2-3g boric acid and 1-2g aluminum nitrate and disperse them in an ethanol aqueous solution, and after the dispersion is uniform, record it as a mixed solution; weigh 5-6g tetraethyl orthosilicate and disperse it in an ethanol aqueous solution, and after the dispersion is uniform, record it as a tetraethyl orthosilicate solution;
[0026] Step 8.2, pour the mixed solution into the ethyl orthosilicate solution, stir evenly and adjust the pH value to 4, then dry at 70°C for 3-4h and then dry at 500°C to constant weight, grind and sieve to obtain the ceramic binder.
[0027] Furthermore, in step 8.1, the volume fraction of the ethanol aqueous solution was 80%, and the specific operation for uniform dispersion was stirring at a speed of 500 r / min for 10 min. In step 8.2, a hydrochloric acid solution with a mass fraction of 10% was added dropwise to adjust the pH value. The specific operation for grinding and sieving was pouring into a ball mill, grinding and passing through a 200-mesh sieve.
[0028] Furthermore, in step 4, the spray drying flow rate is 50 mL / min, the spray drying speed is 30000-40000 r / min, the spray drying temperature is 200-300°C, the baking insulation agglomeration temperature is 750-780°C, and the baking insulation agglomeration insulation time is 2-3h.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. The present invention first etches diamond micropowder with nickel powder, and then performs surface treatment on the diamond micropowder with tetraethyl orthosilicate and zinc nitrate respectively, so as to prepare silanized diamond micropowder with silicon dioxide coating adsorbed on the surface and coated diamond micropowder with zinc oxide coated on the surface, and then add the silanized diamond micropowder and coated diamond micropowder to the diamond micropowder, and combine with ceramic binder and polyvinyl alcohol to prepare agglomerated diamond, which can improve the wear resistance, bonding strength and oxidation resistance of the agglomerated diamond; etching the diamond micropowder with nickel powder can introduce microstructural changes or defects on the surface of the diamond micropowder, which helps the subsequent surface treatment agent to better adhere to the diamond micropowder, and the etching treatment can increase the surface area of the diamond micropowder, thereby improving the bonding ability of the etched diamond micropowder with other substances.
[0031] 2. Ethyl orthosilicate can be hydrolyzed to form silicon dioxide under high temperature or catalyst, thus forming a silicon dioxide coating on the surface of diamond micropowder. This coating not only improves the wear resistance, corrosion resistance and thermal stability of diamond micropowder, but also improves its compatibility with ceramic binder; secondly, zinc nitrate can react with certain components on the surface of diamond micropowder at high temperature to form zinc oxide coating, which also has the function of improving the performance of diamond micropowder, such as enhancing oxidation resistance and improving dispersibility; secondly, both silicon dioxide and zinc oxide coatings can effectively improve the wear resistance of diamond micropowder, making the group Polydiamond can maintain a longer service life during use. Silanization treatment can improve the compatibility of diamond micropowder and ceramic binder, while the zinc oxide coating can enhance the interaction between diamond micropowders, thereby improving the overall bonding strength of the agglomerated diamond. Finally, the zinc oxide coating helps to improve the dispersibility of diamond micropowder in the ceramic binder, avoids the agglomeration of micropowders, and makes the structure of the agglomerated diamond more uniform and dense. Moreover, both silicon dioxide and zinc oxide coatings have good thermal stability and oxidation resistance, which can protect diamond micropowder from damage in high temperature or oxidizing environments.
[0032] 3. The present invention uses sodium nitrate, boric acid, aluminum nitrate and tetraethyl orthosilicate as raw materials to prepare a ceramic binder, which is added to diamond micropowder to prepare agglomerated diamond, which can significantly improve the bonding force, wear resistance and chemical stability of the agglomerated diamond; sodium nitrate, boric acid and aluminum nitrate can form a stable ceramic phase at high temperature, and these ceramic phases have good bonding ability with the diamond micropowder, especially aluminum nitrate, which can react with the carbon element on the surface of the diamond at high temperature to form a carbide layer, thereby further enhancing the bonding force between the diamond micropowder and the ceramic binder. This enhanced bonding force makes the agglomerated diamond more stable during use and not easy to fall off or wear; Secondly, the ceramic phase formed by sodium nitrate, boric acid and aluminum nitrate at high temperature has good heat resistance and can resist thermal shock and thermal stress in high temperature environment. The improvement of heat resistance enables the agglomerated diamond to maintain stable performance in high temperature processing environment and is not prone to thermal deformation or thermal damage. Moreover, tetraethyl orthosilicate can be hydrolyzed to form silicon dioxide at high temperature, which can form a complex silicate network structure with other ceramic components. This network structure helps to fill the gaps between diamond powders and optimize the microstructure of agglomerated diamond, making it denser and more uniform. The dense microstructure helps to improve the hardness and strength of agglomerated diamond while reducing the generation of cracks and defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings are used for further understanding of the present invention and are used to explain the present invention together with the embodiments of the present invention, but do not constitute a limitation of the present invention.
[0034] Figure 1It is an experimental data recording table diagram of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention will be further described below in conjunction with the embodiments. Example 1
[0037] The present embodiment provides a method for preparing agglomerated diamonds, the preparation method comprising the following steps:
[0038] Step 1: etching diamond micropowder with nickel powder to prepare etched diamond micropowder, performing surface silanization treatment on the etched diamond micropowder to prepare silanized diamond micropowder, and then coating the etched diamond micropowder with zinc oxide to prepare coated diamond micropowder.
[0039] The steps for preparing the etched diamond powder are as follows:
[0040] Step 2.1, immerse the diamond powder in a 10% hydrochloric acid solution and boil it for 10 minutes, rinse it with pure water until it is neutral, immerse it in a 10% sodium hydroxide solution and boil it for 10 minutes, rinse it with pure water again until it is neutral, and then dry it at 65°C for 2 hours. The obtained diamond powder is recorded as pre-treated diamond powder;
[0041] Step 2.2, the pretreated diamond powder and nickel powder are mixed in a weight ratio of 1:5 and poured into a quartz boat for compaction, and then the quartz boat is placed in a vacuum tube furnace and heated to 600°C at a heating rate of 10°C / min, and then heated to 900°C at a heating rate of 5°C / min, and then cooled to 300°C at a cooling rate of 10°C / min after keeping the temperature for 1 hour, and then naturally cooled to room temperature, and the obtained result is recorded as a sintered component;
[0042] Step 2.3, immerse the sintered component in aqua regia and stir at a speed of 100 r / min for 30 minutes, then place it in an ultrasonic cleaner and ultrasonically vibrate it at a power of 200 W for 10 minutes, filter and remove the filtrate to obtain the precipitated component, rinse the precipitated component with pure water to neutrality and place it in an oven at 68°C to dry for 3 hours, and the result is etched diamond micropowder.
[0043] The preparation steps of silanized diamond powder are:
[0044] Step 4.1, 5 mL of ethyl orthosilicate and 195 mL of 80% ethanol aqueous solution were stirred at 400 r / min in a water bath at 50° C. for 2 h, and the resultant was recorded as the hydrolyzate component;
[0045] Step 4.2, weigh 2g of etched diamond powder and pour it into the hydrolyzate component, stir and react at a speed of 300r / min in a water bath at 50℃ for 2h to obtain a suspension, and place the suspension at a temperature of 58℃ to evaporate for 24h. The obtained powder is silanized diamond powder.
[0046] The preparation steps of coated diamond powder are as follows:
[0047] Step 5.1, weigh 9 g of zinc nitrate and dissolve it in 300 mL of pure water and stir it at 400 r / min for 10 min, then add 55 g of urea and stir it at 400 r / min for 10 min, finally add 45 mg of sodium dodecyl sulfate and stir it at 400 r / min for 10 min, the result is recorded as zinc nitrate solution;
[0048] Step 5.2, weigh 4g of etched diamond powder and add it to zinc nitrate solution, stir it magnetically at a speed of 500r / min for 30min, then heat it to 80℃, and stir it at a constant temperature at a speed of 300r / min for 2h to react. After the reaction is completed, filter the precipitate, rinse it with pure water until it is neutral, and finally place it in a muffle furnace at a temperature of 300℃ for heat treatment for 2h. After naturally cooling to room temperature, the obtained is coated diamond powder.
[0049] Step 2: Add 9 parts by weight of silanized diamond powder and 8 parts by weight of coated diamond powder to 100 parts by weight of diamond powder, pour into a ball mill and mill at a speed of 600 r / min for 10 minutes to obtain a mixed diamond powder component. Prepare a ceramic binder using sodium nitrate, boric acid, aluminum nitrate and tetraethyl orthosilicate as raw materials.
[0050] The preparation steps of the ceramic binder are as follows:
[0051] Step 8.1, weigh 2g of sodium nitrate, 2g of boric acid and 1g of aluminum nitrate, disperse them in an ethanol aqueous solution with a volume fraction of 80%, and record them as a mixed solution after they are evenly dispersed; weigh 5g of tetraethyl orthosilicate, disperse them in an ethanol aqueous solution with a volume fraction of 80%, and stir them at a speed of 500r / min for 10min, and record them as a tetraethyl orthosilicate solution;
[0052] Step 8.2: Pour the mixed solution into the ethyl orthosilicate solution, stir at a speed of 500 r / min for 10 min, then add a 10% hydrochloric acid solution by mass to adjust the pH value to 4, then dry at 70°C for 3 h, then dry at 500°C to constant weight, pour into a ball mill, grind and pass through a 200-mesh sieve to obtain a ceramic binder.
[0053] Step 3, weigh 30 parts by weight of a mixed diamond powder component and 20 parts by weight of a ceramic binder, pour them into a ball mill and ball mill to obtain a ball mill component, weigh 0.1 parts by weight of polyvinyl alcohol, pour them into 50 parts by weight of pure water, and stir at a speed of 500 r / min for 10 minutes to obtain a solution component.
[0054] Step 4: pour the ball-milled component into the solution component and stir at a speed of 200 r / min for 10 min. After spray drying, bake and insulate for agglomeration. The result after sieving is agglomerated diamond, wherein the spray drying flow rate is 50 mL / min, the spray drying speed is 30000 r / min, the spray drying temperature is 200°C, the baking and insulating agglomeration temperature is 750°C, and the baking and insulating agglomeration insulation time is 2 h. Example 2
[0055] The present embodiment provides a method for preparing agglomerated diamonds, the preparation method comprising the following steps:
[0056] Step 1: etching diamond micropowder with nickel powder to prepare etched diamond micropowder, performing surface silanization treatment on the etched diamond micropowder to prepare silanized diamond micropowder, and then coating the etched diamond micropowder with zinc oxide to prepare coated diamond micropowder.
[0057] The steps for preparing the etched diamond powder are as follows:
[0058] Step 2.1, immerse the diamond powder in a 10% hydrochloric acid solution and boil it for 10 minutes, rinse it with pure water until it is neutral, immerse it in a 10% sodium hydroxide solution and boil it for 10 minutes, rinse it with pure water again until it is neutral, and dry it at 65°C for 3 hours. The obtained diamond powder is recorded as pre-treated diamond powder;
[0059] Step 2.2, the pretreated diamond powder and nickel powder are mixed in a weight ratio of 1:5 and poured into a quartz boat for compaction, and then the quartz boat is placed in a vacuum tube furnace and heated to 600°C at a heating rate of 10°C / min, and then heated to 900°C at a heating rate of 5°C / min, and then cooled to 300°C at a cooling rate of 10°C / min after keeping the temperature for 1 hour, and then naturally cooled to room temperature, and the obtained result is recorded as a sintered component;
[0060] Step 2.3, immerse the sintered component in aqua regia and stir at a speed of 100 r / min for 30 minutes, then place it in an ultrasonic cleaner and ultrasonically vibrate it at a power of 200 W for 10 minutes, filter and remove the filtrate to obtain a precipitated component, rinse the precipitated component with pure water to neutrality and place it in an oven at 68°C to dry for 5 hours, and the result is etched diamond micropowder.
[0061] The preparation steps of silanized diamond powder are:
[0062] Step 4.1, 5 mL of ethyl orthosilicate and 195 mL of 80% ethanol aqueous solution were stirred at 400 r / min in a water bath at 50° C. for 3 h, and the resultant was recorded as the hydrolyzate component;
[0063] Step 4.2, weigh 3g of etched diamond powder and pour it into the hydrolyzate component, stir and react at a speed of 300r / min in a water bath at 80℃ for 4h to obtain a suspension, and place the suspension at a temperature of 58℃ to evaporate for 48h. The obtained powder is silanized diamond powder.
[0064] The preparation steps of coated diamond powder are as follows:
[0065] Step 5.1, weigh 9 g of zinc nitrate and dissolve it in 300 mL of pure water and stir it at 400 r / min for 10 min, then add 55 g of urea and stir it at 400 r / min for 10 min, finally add 45 mg of sodium dodecyl sulfate and stir it at 400 r / min for 10 min, the result is recorded as zinc nitrate solution;
[0066] Step 5.2, weigh 5g of etched diamond powder and add it to zinc nitrate solution, stir it magnetically at a speed of 500r / min for 30min, then heat it to 80℃, and stir it at a constant temperature of 300r / min for 2h to react. After the reaction is completed, filter the precipitate, rinse it with pure water until it is neutral, and finally place it in a muffle furnace at a temperature of 300℃ for heat treatment for 2h. After naturally cooling to room temperature, the obtained is coated diamond powder.
[0067] Step 2: Add 10 parts by weight of silanized diamond powder and 12 parts by weight of coated diamond powder to 100 parts by weight of diamond powder, pour into a ball mill and mill at a speed of 600 r / min for 10 minutes to obtain a mixed diamond powder component. Prepare a ceramic binder using sodium nitrate, boric acid, aluminum nitrate and tetraethyl orthosilicate as raw materials.
[0068] The preparation steps of the ceramic binder are as follows:
[0069] Step 8.1, weigh 3g of sodium nitrate, 3g of boric acid and 2g of aluminum nitrate, disperse them in an ethanol aqueous solution with a volume fraction of 80%, and record them as a mixed solution after they are evenly dispersed; weigh 6g of tetraethyl orthosilicate, disperse them in an ethanol aqueous solution with a volume fraction of 80%, and stir them at a speed of 500r / min for 10min, and record them as a tetraethyl orthosilicate solution;
[0070] Step 8.2, pour the mixed solution into the ethyl orthosilicate solution, stir at a speed of 500 r / min for 10 minutes, then add a 10% hydrochloric acid solution by mass to adjust the pH value to 4, then dry it at 70°C for 4 hours, then dry it at 500°C to constant weight, pour it into a ball mill, grind it and pass it through a 200-mesh sieve to obtain a ceramic binder.
[0071] Step 3, weigh 50 parts by weight of a mixed diamond powder component and 30 parts by weight of a ceramic binder, pour them into a ball mill and ball mill to obtain a ball mill component, weigh 0.2 parts by weight of polyvinyl alcohol, pour them into 20 parts by weight of pure water, and stir at a speed of 500 r / min for 10 minutes to obtain a solution component.
[0072] Step 4: pour the ball-milled component into the solution component and stir at a speed of 200 r / min for 10 min. After spray drying, bake and insulate for agglomeration. The result after sieving is agglomerated diamond, wherein the spray drying flow rate is 50 mL / min, the spray drying speed is 40000 r / min, the spray drying temperature is 300°C, the baking and insulating agglomeration temperature is 780°C, and the baking and insulating agglomeration insulation time is 3h. Example 3
[0073] The present embodiment provides a method for preparing agglomerated diamonds, the preparation method comprising the following steps:
[0074] Step 1: etching diamond micropowder with nickel powder to prepare etched diamond micropowder, performing surface silanization treatment on the etched diamond micropowder to prepare silanized diamond micropowder, and then coating the etched diamond micropowder with zinc oxide to prepare coated diamond micropowder.
[0075] The steps for preparing the etched diamond powder are as follows:
[0076] Step 2.1, immerse the diamond powder in a 10% hydrochloric acid solution and boil it for 10 minutes, rinse it with pure water until it is neutral, immerse it in a 10% sodium hydroxide solution and boil it for 10 minutes, rinse it with pure water again until it is neutral, and dry it at 65°C for 3 hours. The obtained diamond powder is recorded as pre-treated diamond powder;
[0077] Step 2.2, the pretreated diamond powder and nickel powder are mixed in a weight ratio of 1:5 and poured into a quartz boat for compaction, and then the quartz boat is placed in a vacuum tube furnace and heated to 600°C at a heating rate of 10°C / min, and then heated to 900°C at a heating rate of 5°C / min, and then cooled to 300°C at a cooling rate of 10°C / min after keeping the temperature for 1 hour, and then naturally cooled to room temperature, and the obtained result is recorded as a sintered component;
[0078] Step 2.3, immerse the sintered component in aqua regia and stir at a speed of 100 r / min for 30 minutes, then place it in an ultrasonic cleaner and ultrasonically vibrate it at a power of 200 W for 10 minutes, filter and remove the filtrate to obtain the precipitated component, rinse the precipitated component with pure water to neutrality and place it in an oven at 68°C to dry for 4 hours, and the result is etched diamond micropowder.
[0079] The preparation steps of silanized diamond powder are:
[0080] Step 4.1, 5 mL of ethyl orthosilicate and 195 mL of 80% ethanol aqueous solution were stirred at 400 r / min in a water bath at 50° C. for 3 h, and the resultant was recorded as the hydrolyzate component;
[0081] Step 4.2, weigh 3g of etched diamond powder and pour it into the hydrolyzate component, stir and react at a speed of 300r / min in a water bath at 60℃ for 3h to obtain a suspension, and place the suspension at a temperature of 58℃ to evaporate for 36h. The obtained powder is silanized diamond powder.
[0082] The preparation steps of coated diamond powder are as follows:
[0083] Step 5.1, weigh 9 g of zinc nitrate and dissolve it in 300 mL of pure water and stir it at 400 r / min for 10 min, then add 55 g of urea and stir it at 400 r / min for 10 min, finally add 45 mg of sodium dodecyl sulfate and stir it at 400 r / min for 10 min, the result is recorded as zinc nitrate solution;
[0084] Step 5.2, weigh 5g of etched diamond powder and add it to zinc nitrate solution, stir it magnetically at a speed of 500r / min for 30min, then heat it to 80℃, and stir it at a constant temperature of 300r / min for 2h to react. After the reaction is completed, filter the precipitate, rinse it with pure water until it is neutral, and finally place it in a muffle furnace at a temperature of 300℃ for heat treatment for 2h. After naturally cooling to room temperature, the obtained is coated diamond powder.
[0085] Step 2: Add 10 parts by weight of silanized diamond powder and 10 parts by weight of coated diamond powder to 100 parts by weight of diamond powder, pour into a ball mill and mill at a speed of 600 r / min for 10 minutes to obtain a mixed diamond powder component. Prepare a ceramic binder using sodium nitrate, boric acid, aluminum nitrate and tetraethyl orthosilicate as raw materials.
[0086] The preparation steps of the ceramic binder are as follows:
[0087] Step 8.1, weigh 2g of sodium nitrate, 3g of boric acid and 2g of aluminum nitrate, disperse them in an ethanol aqueous solution with a volume fraction of 80%, and record them as a mixed solution after they are evenly dispersed; weigh 6g of tetraethyl orthosilicate, disperse them in an ethanol aqueous solution with a volume fraction of 80%, and stir them at a speed of 500r / min for 10min, and record them as a tetraethyl orthosilicate solution;
[0088] Step 8.2, pour the mixed solution into the ethyl orthosilicate solution, stir at a speed of 500 r / min for 10 minutes, then add a 10% hydrochloric acid solution by mass to adjust the pH value to 4, then dry it at 70°C for 4 hours, then dry it at 500°C to constant weight, pour it into a ball mill, grind it and pass it through a 200-mesh sieve to obtain a ceramic binder.
[0089] Step 3, weigh 40 parts by weight of a mixed diamond powder component and 25 parts by weight of a ceramic binder, pour them into a ball mill and ball mill to obtain a ball mill component, weigh 0.2 parts by weight of polyvinyl alcohol, pour them into 35 parts by weight of pure water, and stir at a speed of 500 r / min for 10 minutes to obtain a solution component.
[0090] Step 4, pour the ball-milled component into the solution component and stir at a speed of 200 r / min for 10 minutes. After spray drying, bake and insulate for agglomeration. The result after sieving is agglomerated diamond, wherein the spray drying flow rate is 50 mL / min, the spray drying speed is 40000 r / min, the spray drying temperature is 250°C, the baking and insulating agglomeration temperature is 770°C, and the baking and insulating agglomeration insulation time is 3 hours.
[0091] Comparative Example 1:
[0092] The method for preparing agglomerated diamond provided in this comparative example is substantially the same as that in Example 1, the main difference is that in this comparative example 1, the etched diamond powder in Example 1 is replaced with diamond powder.
[0093] Comparative Example 2:
[0094] The method for preparing agglomerated diamond provided in this comparative example is substantially the same as that in Example 1, the main difference is that in this comparative example 2, the silanized diamond powder in Example 1 is replaced with diamond powder.
[0095] Comparative Example 3:
[0096] The method for preparing agglomerated diamond provided in this comparative example is substantially the same as that in Example 1, the main difference is that in this comparative example 3, the coated diamond powder in Example 1 is replaced with diamond powder.
[0097] Comparative Example 4:
[0098] The method for preparing agglomerated diamond provided in this comparative example is substantially the same as that in Example 1, the main difference being that the ceramic binder in Example 1 is replaced with boron glass in this comparative example 4.
[0099] Performance Test:
[0100] The agglomerated diamonds prepared in Examples 1-3 and Comparative Examples 1-4 are marked as Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, respectively. Then, the bending strength, hardness and flexural strength of Examples 1-3 and Comparative Examples 1-4 are tested, and the obtained data are recorded in Figure 1 ;
[0101] pass Figure 1 The data show that the bending strength, hardness and flexural strength of the agglomerated diamonds in Examples 1-3 are higher than those in Comparative Examples 1-4, indicating that etching the diamond powder and then modifying its surface can make the modified diamond powder have better mechanical properties. It also shows that doping the diamond powder with silanized diamond powder and coated diamond powder can make the prepared agglomerated diamond have higher bending strength and flexural strength, and the addition of the ceramic binder prepared in the present invention can make the prepared agglomerated diamond have higher hardness. In summary, the agglomerated diamond prepared in the present invention has excellent market promotion value and market application prospects.
[0102] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0103] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing agglomerated diamond, characterized in that: The preparation method comprises the following steps: Step 1, etching diamond micropowder with nickel powder to prepare etched diamond micropowder, performing surface silanization treatment on the etched diamond micropowder to prepare silanized diamond micropowder, and then coating the etched diamond micropowder with zinc oxide to prepare coated diamond micropowder; Step 2, adding 9-10 parts by weight of silanized diamond powder and 8-12 parts by weight of coated diamond powder to 100 parts by weight of diamond powder, mixing the mixture evenly to obtain a mixed diamond powder component, and preparing a ceramic binder using sodium nitrate, boric acid, aluminum nitrate and tetraethyl orthosilicate as raw materials; Step 3, weighing 30-50 parts by weight of a mixed diamond powder component and 20-30 parts by weight of a ceramic binder, pouring them into a ball mill to obtain a ball-milled component, weighing 0.1-0.2 parts by weight of polyvinyl alcohol, pouring them into 20-50 parts by weight of pure water, and stirring at a speed of 500 r / min for 10 minutes to obtain a solution component; Step 4, pouring the ball mill component into the solution component and stirring at a speed of 200r / min for 10min, spray drying, baking and heat preservation for agglomeration, and the agglomerated diamond obtained after sieving; In step 1, the preparation steps of silanized diamond powder are: Step 4.1, 5 mL of ethyl orthosilicate and 195 mL of 80% ethanol aqueous solution were stirred at 400 r / min in a water bath at 50°C for 2-3 h, and the resultant was recorded as the hydrolyzate component; Step 4.2, weigh 2-3g of etched diamond powder and pour it into the hydrolyzate component, stir and react at a speed of 300r / min in a water bath at 50-80°C for 2-4h to obtain a suspension, and place the suspension at a temperature of 58°C to evaporate for 24-48h. The obtained powder is silanized diamond powder; In step 1, the preparation steps of coated diamond powder are: Step 5.1, weigh 9 g of zinc nitrate and dissolve it in 300 mL of pure water and stir until dissolved, then add 55 g of urea and stir until dissolved, and finally add 45 mg of sodium dodecyl sulfate and stir until dissolved, the result is recorded as zinc nitrate solution; Step 5.2, weigh 4-5g of etched diamond powder and add it to zinc nitrate solution, stir magnetically for 30min, heat to 80°C, and stir at constant temperature for 2h to react. After the reaction is completed, filter to obtain a precipitate, rinse with pure water until neutral, and finally place it in a muffle furnace at 300°C for 2h. After naturally cooling to room temperature, the obtained is coated diamond powder; In step 2, the preparation steps of the ceramic binder are: Step 8.1, weigh 2-3g sodium nitrate, 2-3g boric acid and 1-2g aluminum nitrate and disperse them in an ethanol aqueous solution, and after the dispersion is uniform, record it as a mixed solution; weigh 5-6g tetraethyl orthosilicate and disperse it in an ethanol aqueous solution, and after the dispersion is uniform, record it as a tetraethyl orthosilicate solution; Step 8.2, pour the mixed solution into the ethyl orthosilicate solution, stir evenly and adjust the pH value to 4, then dry at 70°C for 3-4h and then dry at 500°C to constant weight, grind and sieve to obtain the ceramic binder.
2. The method for preparing agglomerated diamond according to claim 1, characterized in that: In step 1, the preparation steps of etched diamond powder are: Step 2.1, immerse the diamond powder in a hydrochloric acid solution and boil it for 10 minutes, rinse it with pure water until it is neutral, immerse it in a sodium hydroxide solution and boil it for 10 minutes, rinse it with pure water again until it is neutral, and then dry it. The result is recorded as pre-treated diamond powder; Step 2.2, the pretreated diamond powder and nickel powder are mixed in a weight ratio of 1:5 and poured into a quartz boat for compaction, and then the quartz boat is placed in a vacuum tube furnace and heated to 600°C at a heating rate of 10°C / min, and then heated to 900°C at a heating rate of 5°C / min, and then cooled to 300°C at a cooling rate of 10°C / min after keeping the temperature for 1 hour, and then naturally cooled to room temperature, and the obtained result is recorded as a sintered component; Step 2.3, immerse the sintered component in aqua regia and stir at a speed of 100 r / min for 30 minutes, then place it in an ultrasonic cleaner for ultrasonic oscillation, filter and remove the filtrate to obtain a precipitated component, rinse the precipitated component with pure water to neutrality and dry it to obtain etched diamond micropowder.
3. The method for preparing agglomerated diamond according to claim 2, characterized in that: In step 2.1, the mass fraction of the hydrochloric acid solution is 10%, the mass fraction of the sodium hydroxide solution is 10%, and the specific operation of the drying treatment is to dry it at a temperature of 65°C for 2-3 hours. In step 2.3, the specific operation of the ultrasonic oscillation is to ultrasonically oscillate at a power of 200W for 10 minutes, and the specific operation of the drying treatment is to dry it in an oven at 68°C for 3-5 hours.
4. The method for preparing agglomerated diamond according to claim 1, characterized in that: In step 5.1, the specific operation of stirring until dissolved is stirring at a speed of 400 r / min for 10 min. In step 5.2, the speed of magnetic stirring is 500 r / min, and the speed of constant temperature stirring is 300 r / min.
5. The method for preparing agglomerated diamond according to claim 1, characterized in that: In step 2, the specific operation of mixing uniformly is pouring into a ball mill and ball milling at a rotation speed of 600 r / min for 10 minutes.
6. The method for preparing agglomerated diamond according to claim 1, characterized in that: In step 8.1, the volume fraction of the ethanol aqueous solution was 80%, and the specific operation for uniform dispersion was stirring at a speed of 500 r / min for 10 min. In step 8.2, a hydrochloric acid solution with a mass fraction of 10% was added dropwise to adjust the pH value. The specific operation for grinding and sieving was pouring into a ball mill, grinding and passing through a 200-mesh sieve.
7. The method for preparing agglomerated diamond according to claim 1, characterized in that: In step 4, the flow rate of spray drying is 50 mL / min, the speed of spray drying is 30000-40000 r / min, the temperature of spray drying is 200-300° C., the temperature of baking and heat preservation agglomeration is 750-780° C., and the insulation time of baking and heat preservation agglomeration is 2-3 h.
Citation Information
Patent Citations
Method for preparing inorganic heat-conducting adhesive by taking etched diamond micro powder as filler
CN113999617A